Integration of Zakat and Takaful: The Scheme for Optimizing the Welfare of Low-Income Communities - Azizah, Azizah (Center of Strategic Studies (PUSKAS) BAZNAS, 2025)
This study aims to explore the opportunity of zakat to be integrated with takaful in order to expand the impact on well-being of underprivileged communities. Although the literature review on zakat and takaful integration is still limited, the authors managed to identify 13 scientific articles sourced from reputable journal databases, namely Web of Science, Dimensions, Emerald, and Scopus. The articles were processed using Systematic Reviews and Meta-analyses (PRISMA). The review of 13 selected articles identified the urgency of the need for microtakaful products in low-income groups, the scheme applied in the implementation of the integration of zakat and takaful, and fiqh studies on the integration of the two. This research is expected to provide insights for further research. This research seeks to fill the gap in the existing literature by specifically highlighting the potential of zakat in showing its role as an Islamic financial instrument that is relevant to the needs of today's society and has a positive impact on the welfare of underprivileged communities. In addition, the findings imply that integrating zakat with microtakaful could serve as a viable policy approach to strengthen financial inclusion and resilience among low-income groups.